Masail fiqhiyah al haditsah pada masalah masalah kontemporer hukum Islam - M. Ali Hasan (Raja Grafindo Persada, 1997)
oen, c.1/oen, c.2-3/ir,c.4/oen, c.5-6/oen, c.7/oen, c.8/oen, c.9/oen, c.10/wk, c.11/wk, c.12/ir,c.13-14/ir,c.15